Achieving company goals through general affairs management / Athiyya Hikmariada, Amaliyah and Rahmat Yuliawan - Hikmariada, Athiyya; ., Amaliyah; Yuliawan, Rahmat (Universiti Teknologi MARA, Cawangan Melaka, 2022)
Every company has human resources who play a vital role in organizing and moving the company. The objective of this study is to determine how the role of General Affair in Asset Management at PT Industri Kereta Api (Persero) to be efficient and effective. One of them is the role of General Affairs which has a vital role in asset management in the company. PT INKA Madiun has many assets used to support the company's production activities. Therefore, asset management is needed to ensure all assets are always in good condition. The General Affairs Department carries out asset management at PT INKA Madiun. The data collection method used is by conducting interviews, observations, and literature studies. Based on the observations, it can be concluded that the role of the General Affairs Department as asset manager includes planning for procurement, maintenance, management, and write-off of production assets and nonproduction assets. The role of asset management has been carried out well, but there are still some obstacles to its implementation. Constraints found when managing assets are related to facilities. Asset management activities are mostly done manually rather than utilizing existing technology. Therefore, it is necessary to improve procedures for staff, apply integrated technology and provide adequate facilities for employees so that their role in asset management will be more optimal.